Association Between Breastfeeding Frequency and Neonatal Jaundice in the Perinatology Unit of Bhayangkara Hospital Bondowoso - Faizah, Anik Ummi; Fatkuriyah, Lailil; Sukowati, Umi (Journal of Nursing Periodic, 2025)
Introduction: Low frequency of breastfeeding (<8 times per day) can reduce the infant's body fluid volume, thereby hindering bilirubin excretion and resulting in reabsorption into the bloodstream. This condition increases bilirubin levels and the risk of neonatal jaundice. If not properly managed, jaundice can develop into kernicterus, a condition of permanent brain damage caused by the accumulation of bilirubin in brain tissue. In Indonesia, the incidence rate of hyperbilirubinemia is 79.6%. At Bhayangkara Hospital Bondowoso in 2024, 25.7% of newborns experienced jaundice. This study aims to analyze the relationship between breastfeeding frequency and the incidence of neonatal jaundice in the Perinatology Unit of Bhayangkara Hospital Bondowoso. Methods: This is a quantitative study with a cross-sectional design. The population consisted of all mothers who gave birth at Bhayangkara Hospital Bondowoso, totaling 103 individuals. The sample size was calculated using the Slovin formula, resulting in 83 respondents selected through purposive sampling. Results: The results showed that the majority of respondents (54%) breastfed with a low frequency (<8 times per day), while 46% breastfed frequently (≥8 times per day). Furthermore, 53% of infants experienced jaundice, while 47% did not. Based on the chi-square statistical test, there was a significant relationship between breastfeeding frequency and the incidence of neonatal jaundice at Bhayangkara Hospital Bondowoso, with a p-value of 0.000 (<0.05). Conclusions: This indicates that the lower the frequency of breastfeeding, the higher the risk of jaundice in newborns. The findings of this study are expected to serve as a foundation for enhancing education for breastfeeding mothers to prevent jaundice in newborns. Keywords: Breastfeeding frequency, neonatal jaundice